A third species of the Trisinus cavernosus group (Coleoptera: Staphylinidae: Pselaphinae) - Ding, Mei-Lin; Ming, Liang; Yin, Zi-Wei (Zootaxa, 2025)
Trisinus tangliangi Ding, Ming & Yin, sp. nov. is described from Shenzhen, South China, which represents a third member of the T. cavernosus Ding, Niu & Yin species group. The new species shares the characteristic male cephalic excavation and aedeagal structures typical of the group, and can be readily distinguished from both congeners by the significantly more laterally dilated head and pronotum.